THE EFFECT OF TWO BODY CORRELATIONS ON THE CHARGE DENSITY DISTRIBUTIONS AND ELASTIC ELECTRON SCATTERING FORM FACTORS FOR SOME 2s-1d SHELL NUCLEI - Hamoudi, A K; Radhi, R A; Flaiyh, G N; Shrrad, F I (Al-Nahrain Journal of Science, 2018)
An effective two-body density operator for point nucleon system folded with two-bodycorrelation functions, which take account of the effect of the strong short range repulsion and thestrong tensor force in the nucleon-nucleon forces, is produced and used to study the ground statetwo-body charge density distributions (r ) ch and elastic electron scattering form factors F (q) for2s -1d shell nuclei with Z = N (such as 20Ne, 24Mg, 28Si and 32S nuclei). It is found that theinclusion of the two-body short range correlations (SRC) has the feature of reducing the central partof (r ) ch significantly and increasing the tail part of (r ) ch slightly, i.e., it tends to increase theprobability of transferring the protons from the central region of the nucleus towards its surface andto increase the root mean square charge radius < r 2 >1/ 2 of the nucleus and then makes the nucleusto be less rigid than the case when there is no SRC. It is also found that the effects of two bodytensor correlations (TC) on (r ) ch and < r 2 >1/ 2 are in opposite direction to those of SRC.